Unintended Consequences of U. S. Monetary Policy Shocks : Dutch Disease and Capital Flow Measures in Emerging Markets and Developing Economies - Yepez, Juan (IMF Working Papers; Working Paper ;, 2021)
Dutch disease is often referred as a situation in which large and sustained foreign currency inflows lead to a contraction of the tradable sector by giving rise to a real appreciation of the home currency. This paper documents that this syndrome has been witnessed by many emerging markets and developing economies (EMDEs) as a result of surges in capital inflows driven by accommodative U. S. monetary policy. In a sample of 25 EMDEs from 2000-17, U. S. monetary policy shocks coincided with episodes of currency appreciation and a contraction in tradable output in these economies. The paper also shows empirically that the use of capital flow measures (CFMs) has been a common policy response in several EMDEs to U.S. monetary policy shocks. Against this background, the paper presents a two sector small open economy augmented with a learning-by-doing (LBD) mechanism in the tradable sector to rationalize these empirical findings. A welfare analysis provides a rationale for the use of CFMs as a second-best policy when agents do not internalize the LBD externality of costly resource misallocation as a result of greater capital inflows. However, the adequate calibration of CFMs and the quantification of the LBD externality represent important implementation challenges.